Asuhan Keperawatan Pada Klien Diabetes Mellitus Dengan Masalah Keperawatan Gangguan Integritas Kulit Di RSUD Dr. Chasbullah Abdulmadjid Kota Bekasi Tahun 2019 - Asnawati .; Cusmarih . (JURNAL KESEHATAN BHAKTI HUSADA, 2020)
Introduction: Based on the prevalence of diabetes mellitus (DM) which is quite high in the Mayperiod at RSUD dr. Chasbullah Abdul Madjid the city of Bekasi is ranked first of 10 internal diseasesor around 26.75% and the purpose of this scientific paper is to explore nursing care in patients withdiabetes mellitus with nursing problems impaired skin integrity in the azalea room of RSUD Dr.Chasbullah Abdul Madjid Bekasi City. Methodology: The research method used was a case study,where the research was conducted at RSUD dr. Chasbullah Abdul Madjid Bekasi City was held for 3days. The study subjects used 2 clients with medical diagnosis of diabetes mellitus, female sex.Results: After conducting the study, it was found that between patients one and two the developmentof the wound was better, that was in patient 1 than in patient 2. Patient 1 had the dead tissue peeledoff, the wound appeared reddish, and had not smelled. While the patient's 2 dead tissue was stillpartially peeled off, the wound appeared only slightly reddish, did not smell. Conclusion: Patient 1after getting the same intervention and implementation the wound condition does not smell, dead skintissue has been removed and in patient 2 the wound condition does not smell, but there are still somedead tissue that is still attached.